ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN JASA PADA CREDIT UNION (CU) PANCUR KASIH KEMBAYAN, KECAMATAN KEMBAYAN KABUPATEN SANGGAU - B11108045, Marsudi (Jurnal Manajemen Update, 2013)
This study was conducted by taking the title "Analysis of Service Quality Of Services Customer Satisfaction At CU Pancur Love Kembayan District Kembayan the District". Problems studied in this research is "What level of customer satisfaction to service quality at CU Pancur Kembayan Love". The study was conducted using a survey method. The number of samples in this study is the sample amounted to 50 people from a total population of 1947 people, while the variables of study include: physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), guarantee (assurance), empathy (empathy), and analyzes were performed by using analysis of the importance and performance analysis quadrants or cartesian diagram. The results of this research are that, first: is generally known that the respondents were satisfied with the services at CU Pancur Love Kembayan. It can be inferred from the average index value indicates the level of importance value of 4.41, while the average index level of performance showed a value of 3.55. second: Factors assessed respondents satisfactory in service delivery at CU Pancur Love Kembayan and has done well is as follows: the appearance of the staff were immaculate, the staff has extensive knowledge of the credit union, trained staff, staff who could be trusted, and familiar names -name customers. Third: Based on Cartesian diagram obtained results that the aspects that need to be given priority treatment and have not done so well is the condition of the waiting room is clean, completeness communications equipment available, and rapid response to customer demand. Keywords: Quality of Service and Customer Satisfaction,